Aprovechamiento de los residuos de café (Coffea arabica) y maíz (Zea mays) para la elaboración de bolsas biodegradables, ESPAM MFL - Toala Loor, María Fernanda (2019)
The research focuse on the development of biodegradable bags using coffee (Coffea arabica) and corn (Zea mays) waste. In the preparation of the biodegradable sheets, water, gliceryn and vinegar were used as plasticizers for the bioplastic for the formation of the bioplastic. A completely randomize DCA desing was usaed, with 4 treatments composet of coffee residues (grain, skin,mucilage and parchment) and corn (leaves,seeds, corncobs and husks) with different doses (85%) corn and (15%) coffee , (70%) corn and (30%) coffee, (30%) corn and (70%) coffee, (85%) coffee and (15%) corn; which were subjected to physical analysis such as biodegradation, solubility, filtration, traction and elongation; the T1 whit the higher concentracion of corn residue (85%) compared to coffe (15%) stood out in terms of physical test, obtaining a lowerpercentageof solubility (16%), no water filtration and higher percentage of elongation (28%) with a atraction pf 0,66 MPa and its biodegradation was greater than 70% in 6 weeks of monitoring. This was the treatment chosen to prepare the biodegradable bag, whose dimension was 22x15 cm. The treatment whit the lowest characteristic was T4 (85% coffee and 15% corn) whit a feater amount of lipids and sucrose, whitc affeted the resistance of the sheet. Which the results obtained, the hypothesis raised is rejected because it does not meet the physical requirements (elongation and traction) stipulated in the NTE INEN 2290-2015-12 standard of plastic covers for residues and solid waste.